KIR Receptors as Key Regulators of NK Cells Activity in Health and Disease - Joanna Dębska-Zielkowska; Grażyna Moszkowska; Maciej Zieliński; Hanna Zielińska; Anna Dukat-Mazurek; Piotr Trzonkowski; Katarzyna Stefańska (Cells, 2021)
Natural killer (NK) cells are part of the cellular immune response. They target mainly cancer and virally infected cells. To a high extent cytotoxic activity of NK cells is regulated inter alia by signals from killer immunoglobulin-like receptors (KIR). The major histocompatibility complex (MHC) class I molecules are important ligands for KIR receptors. Binding of ligands (such as MHC I) to the KIR receptors has the important role in solid organ or hematopoietic cell transplantation. Of note, the understanding of the relationship between KIR and MHC receptors may contribute to the improvement of transplant results. Donor-recipient matching, which also includes the KIR typing, may improve monitoring, individualize the treatment and allow for predicting possible effects after transplantation, such as the graft-versus-leukemia effect (GvL) or viral re-infection. There are also less evident implications of KIR/MHC matching, such as with pregnancy and cancer. In this review, we present the most relevant literature reports on the importance of the KIR/MHC relationship on NK cell activity and hematopoietic stem cell transplantation (HSCT)/solid organ transplantation (SOT) effects, the risk of allograft rejection, protection against post-transplant cytomegalovirus (CMV) infection, pregnancy complications, cancer and adoptive therapy with NK cells.